Simulation study of the plastic floor tile for two plate and three plate mold using plastic simulation software - Hudzaifah, Mohd Azam (2008)
This project presents the Simulation Study of the Plastic floor tile for Two plate and Three plate mold using Plastic simulation software. The product design the analysis is hexagonal in shape, and has interlocking features for attaching purpose. The product was designed using Solidwork software, Version 2005. Analyzing of the product was completed using Moldflow software, which is specialize in simulating the broadest range of injection molding processes to predict and avoid potential manufacturing defects. For the analysis in this paper, the Moldflow Plastic Adviser is used as the main software for analyzing the product designed. The perimeter to consider in this study is the two plate and three plate mold type of cold runner injection molding. The three plate mold is believed to be better than two plate mold in term of mass production and quality. The injection perimeters to be considered are actual filling time, actual injection pressure, cycle time, maximum clamping force during cycle, runner system volume and shot volume. The best type of mold with the best injection parameters that save cost is selected to produce the product, which is a plastic floor tile for sport usage.